2006
DOI: 10.1074/jbc.m509848200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Tradeoff between Metabolic and Stress-response Programs in Pseudomonas putida KT2440 Cells Exposed to Toluene

Abstract: When Pseudomonas putida KT2440 cells encounter toluene in the growth medium, they perceive it simultaneously as a potential nutrient to be metabolized, as a membrane-damaging toxic drug to be extruded, and as a macromolecule-disrupting agent from which to protect proteins. Each of these inputs requires a dedicated transcriptional response that involves a large number of genes. We used DNA array technology to decipher the interplay between these responses in P. putida KT2440 subjected to a short challenge (15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 60 publications
10
184
0
Order By: Relevance
“…The gene coding for the flagellar hook-length protein was downregulated. A relationship between flagella and solvent tolerance has been reported previously in solvent-tolerant P. putida strains Segura et al 2001;Dominguez-Cuevas et al 2006). In each case, different flagella genes were found to influence solvent tolerance.…”
Section: Responses Connected To Toluene Tolerance Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation
“…The gene coding for the flagellar hook-length protein was downregulated. A relationship between flagella and solvent tolerance has been reported previously in solvent-tolerant P. putida strains Segura et al 2001;Dominguez-Cuevas et al 2006). In each case, different flagella genes were found to influence solvent tolerance.…”
Section: Responses Connected To Toluene Tolerance Mechanismsmentioning
confidence: 97%
“…Only overexpression of MarA led to increased solvent tolerance, which confirmed earlier observations that this gene is involved in solvent tolerance. Dominguez-Cuevas et al (2006) assessed the transcriptional response of P. putida KT2440[pWW0] to a shock treatment with toluene, o-xylene and 3-methylbenzoate in batch cultures. They concluded that this toluene-degrading strain responds to toluene as a stressor rather than a nutrient.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Some of the changes that can occur in the membrane, when bacteria are exposed to hydrophobic solvents, include vesicle formation, alteration of phospholipid composition, and reduced permeability of the cell membrane (Heipieper & De Bont, 1994; Nicolaou, Gaida, & Papoutsakis, 2010; Ramos et al, 2002). The mechanisms behind tolerance in the model strain P. putida KT2440 has also been studied for different compounds (Benndorf, Thiersch, Loffhagen, Kunath, & Harms, 2006; Domínguez‐Cuevas, González‐Pastor, Marqués, Ramos, & de Lorenzo, 2006; Fernandez, Conde et al, 2012; Fernandez, Niqui‐Arroyo, Conde, Ramos, & Duque, 2012; Roca, Rodríguez‐Herva, Duque, & Ramos, 2008; Santos, Benndorf, & Sá‐Correia, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Among Pseudomonas, Pseudomonas putida has been extensively studied for its aromatic degradation capability, which has made it a model organism in studies relating to aromatic degradation by microbes (Ramos et al, 1997). The toluene degradation pathway (TOL pathway) in P. putida is one of the most studied pathways in terms of transcriptional regulation and expression (Domínguez-Cuevas et al, 2006;Ramos et al, 1997;Silva-Rocha et al, 2011). In spite of significant information being available on the genomic determinants of aromatic degradation by P. putida, there is limited information on the phenotypic attributes influencing its aromatic utilization capability.…”
Section: Introductionmentioning
confidence: 99%